2007
DOI: 10.1002/elan.200703872
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase Immobilization on 3‐Mercaptopropionic Acid Self Assembled Monolayer for Determination of Pesticides

Abstract: Studies on the immobilization of acetylcholinesterase onto a SAM gold electrode and the use of the fabricated biosensor for the determination of carbaryl and parathion are presented. The influence of pH, ionic strength, enzyme loading and concentration of glutaraldehyde on the response of the biosensor was investigated . The amperometric biosensor developed in this study provided linearity to parathion and carbaryl in the 2.0 a 30.0 Â 10 À6 mol L À1 concentration range. The detection limits under the optimum w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…The obtained results were in full agreement with those from HPLC analysis (Cesarino et al 2012). Pedrosa et al (2007) reported on an acetylcholinesterase (AchE)-based amperometric biosensor developed by immobilization onto a self-assembled modified (SAM) gold electrode. Cyclic voltammetric experiments performed with the SAM-AchE biosensor in phosphate buffer solutions, containing acetylthiocholine, confirmed the formation of thiocholine and its electrochemical oxidation at +0.28 V vs Ag/AgCl.…”
Section: Pesticide Biosensorssupporting
confidence: 88%
“…The obtained results were in full agreement with those from HPLC analysis (Cesarino et al 2012). Pedrosa et al (2007) reported on an acetylcholinesterase (AchE)-based amperometric biosensor developed by immobilization onto a self-assembled modified (SAM) gold electrode. Cyclic voltammetric experiments performed with the SAM-AchE biosensor in phosphate buffer solutions, containing acetylthiocholine, confirmed the formation of thiocholine and its electrochemical oxidation at +0.28 V vs Ag/AgCl.…”
Section: Pesticide Biosensorssupporting
confidence: 88%
“…The analytical performances obtained are competitive with the ones reported in literature using, for instance, cobalt phthalocyanine modified carbon epoxy composite with AChE immobilized on nylon net (LOD equal to 12 ppb for paraoxon) [44], AChE biosensor based on a polishable 7,7,8,8-tetracyanoquinodimethane-modified graphite-epoxy biocomposite (LOD equal to 27.5 for paraoxon) [45], AChE captured in a gelatin membrane coupled with carbon screenprinted electrode (LOD equal to 2.5 ppb for paraoxon) [46], AChE immobilized by glutaraldeyde onto carbon screen-printed electrode modified with Prussian Blue (50% of degree of inhibition for paraoxon 25 ppb) [13]. The results found in this work are also satisfactory when compared with AChE immobilized onto a SAM gold electrode (LOD equal to 9.3 ppb for parathion) [22] with the advantage in the case of gold screen-printed electrodes that they are mass produced and cost-effective thus suitable for a single measurement, property very useful in the case of irreversible inhibition based biosensors.…”
Section: Paraoxon Detection In Standard Solutions and In Water Real Smentioning
confidence: 59%
“…Somerset et al have developed a gold electrode modified with mercaptobenzothiazole and either poly(o-methoxyaniline) or poly(2,5-dimethoxyaniline) [19,20]. An AChE based amperometric biosensor was developed by immobilizing the enzyme onto a self assembled modified gold electrode using 3-mercaptopropionic acid, glutaraldehyde or (N -cyclohexy-N -(2-morpholinoethyl)carbodiimide)methyl-ptoluenesulphonate by Pedrosa et al [21,22]. An AChE biosensor was also constructed by means of gold nanoparticles and cysteamine assembled on glassy carbon paste [23] or by single walled carbon nanotubes wrapped by thiol terminated single strand oligonucleotide (ssDNA) on gold [24].…”
Section: Introductionmentioning
confidence: 99%
“…Somerset et al have developed a gold electrode modified with mercaptobenzothiazole and either poly(o-methoxyaniline) or poly(2,5-dimethoxyaniline) [128,129]. An AChE based amperometric biosensor was developed by immobilisation of the enzyme onto a self assembled modified gold electrode using as 3-mercaptopropionic, glutaraldehyde and (N'-cyclohexy-N'-(2-morpholinoethyl) carbodiimide methyl-p-toluenesulfonate by Pedrosa et al [130,131]. The acetylcholinesterase biosensor was also constructed by means of gold nanoparticles and cysteamine assembled on glassy carbon paste [132] or by single walled carbon nanotubes wrapped by thiol terminated single strand oligonucleotide (ssDNA) on gold [133].…”
Section: Immobilisationmentioning
confidence: 99%